2017
DOI: 10.1016/j.egypro.2017.08.141
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal analysis of technical solutions for insulating the opaque building envelope

Abstract: The application of insulating materials for energy refurbishment of buildings improves the thermal transmittance of the envelope. However, if not properly planned and realized, it could reduce the wall's drying potential, modifying its original features and leaving it generally more humid. This can lead to moisture damages, humid insulation material and risk of mould growth. To avoid any problem related to the increased presence of water in the building envelope, it becomes therefore essential to perform the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Additionally, saturation pressure is only dependent on temperature, as shown by the dotted line in Figure 8. As a result of this graphical method, by comparing the vapor saturation and distribution, in the upper part of the roof, the vapor pressure is higher than the saturation vapor pressure, so the blue highlighted color in Figure 8 shows where condensation can be expected [103,104]. This simple, one-dimensional, steady-state calculation approach has been implemented in standards and codes in Europe, the USA, and Canada.…”
Section: Advancements From Glaser Methods To En Iso 15026mentioning
confidence: 99%
“…Additionally, saturation pressure is only dependent on temperature, as shown by the dotted line in Figure 8. As a result of this graphical method, by comparing the vapor saturation and distribution, in the upper part of the roof, the vapor pressure is higher than the saturation vapor pressure, so the blue highlighted color in Figure 8 shows where condensation can be expected [103,104]. This simple, one-dimensional, steady-state calculation approach has been implemented in standards and codes in Europe, the USA, and Canada.…”
Section: Advancements From Glaser Methods To En Iso 15026mentioning
confidence: 99%
“…The ray tracing methodology presented in Section 2.3 based on the model introduced in [17] computes the radiation distribution in the LCE for each mean solar position, which subsequently serves as an input variable for the dynamic heat transfer simulation. Common building simulation software, such as WUFI ® or IDA ICE, often uses one-dimensional model equations [30][31][32] without any ray tracing simulation capability to compute the heat transport in wall structures. Therefore, in order to utilize the solar selective properties of SATIS in 1D simulation tools, a simplified computational methodology is required.…”
Section: Simplified Computational Methodology For 1d Simulation Toolsmentioning
confidence: 99%
“…If all the variables have to be taken into account (influence of solar radiation, incidence of rain on vapour migration and phenomena related to the drying of structures), the dynamic method must be used. However, in this study, to distinguish between cases in which condensation does or does not appear, the static regime can be used, as this method is more conservative for the construction typologies studied [36]. Cascione et al [36] carried out a study of condensations in different building typologies in two Italian cities using both methods.…”
Section: Methodsmentioning
confidence: 99%
“…However, in this study, to distinguish between cases in which condensation does or does not appear, the static regime can be used, as this method is more conservative for the construction typologies studied [36]. Cascione et al [36] carried out a study of condensations in different building typologies in two Italian cities using both methods. From this, they found that with the method of the UNE EN ISO 13788:2016 standard, condensations occur in cases that do not occur with the method of the UNE EN 15026:2007 standard.…”
Section: Methodsmentioning
confidence: 99%